2011
DOI: 10.2174/138161211796904777
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Therapeutics for Cardioprotection

Abstract: Mitochondria represent approximately one-third of the mass of the heart and play a critical role in maintaining cellular function—however, they are also a potent source of free radicals and pro-apoptotic factors. As such, maintaining mitochondrial homeostasis is essential to cell survival. As the dominant source of ATP, continuous quality control is mandatory to ensure their ongoing optimal function. Mitochondrial quality control is accomplished by the dynamic interplay of fusion, fission, autophagy, and mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 330 publications
(420 reference statements)
0
26
0
Order By: Relevance
“…Consistently, another study demonstrated that cilostazol and its analogs exerted a strong protection against apoptotic cell death in HUVECs by scavenging hydroxyl radicals and intracellular ROS with reduction in TNF-a formation [20]. Mitochondria represent approximately one-third of the mass of the heart and play a critical role in maintaining cellular function [21]. Mitochondrial dysfunction has been suggested as a potential cause for heart failure.…”
Section: Discussionmentioning
confidence: 83%
“…Consistently, another study demonstrated that cilostazol and its analogs exerted a strong protection against apoptotic cell death in HUVECs by scavenging hydroxyl radicals and intracellular ROS with reduction in TNF-a formation [20]. Mitochondria represent approximately one-third of the mass of the heart and play a critical role in maintaining cellular function [21]. Mitochondrial dysfunction has been suggested as a potential cause for heart failure.…”
Section: Discussionmentioning
confidence: 83%
“…Using a mouse model, Qian et al demonstrated that heat stress caused mitochondrial injury in cardiomyocytes and activated the mitochondria-mediated cell apoptosis pathway [4]. Due to the high energy consumption of the heart, mitochondria occupy up to 30% of the total volume in cardiomyocytes [5]. Mitochondria are vulnerable to cellular stress, such as heat stress [4], and damaged mitochondria have been suggested to be the key mediator of cardiac apoptosis, which releases cytochrome c and excessive reactive oxygen species (ROS) leading to cell apoptosis pathway activation [6].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] This, in turn, has ushered onto the stage a broad range of mitochondrial therapeutics which function through different mechanisms, in addition to the recognition that established therapeutics, such as metformin, modulate bioenergetics. [12][13][14][15][16][17] The role of mitochondria has also developed well beyond simply providing ATP to the cell to encompass a complex retrograde signaling pathway to the nucleus. [18][19][20] The mechanisms through which this occurs are still not clear, but have been shown in several cases to involve the controlled generation of superoxide and hydrogen peroxide from the respiratory chain.…”
Section: The Emerging Theme Of Redox Bioenergetics In Health and Diseasementioning
confidence: 99%
“…[57] From a therapeutic perspective, the need to control mitochondrial ROS and the associated signaling has resulted in several different strategies to modulate mitochondrial ROS generation both with small molecules and using molecular biology approaches. [12,13,15,[58][59][60] The matrix of the mitochondrion is highly negatively charged and this has been exploited in a series of compounds using a delocalized cationic charge to transport functional pharmacophores into the mitochondrion. The best understood of these compounds is mitochondrially targeted ubiquinone or MitoQ, which is well tolerated in human subjects.…”
Section: Mechanisms Of Mitochondrial Reactive Oxygen Species and Thermentioning
confidence: 99%